2009
DOI: 10.1016/j.tet.2009.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Hemisynthesis and absolute configuration of novel 6-pentyl-2H-pyran-2-one derivatives from Trichoderma spp.

Abstract: a b s t r a c tA comparative study of the secondary metabolism of two Trichoderma spp. with that of the Thctf1 transcription factor gene null mutant of Trichoderma harzianum 34 was carried out in order to deepen our knowledge of the biosynthetic pathway and mode of action of 6-pentyl-2H-pyran-2-one (1) and its derivatives as biocontrol agents. New isolated metabolites have shed light on the detoxification mechanism of 6-pentyl-pyranone by Trichoderma spp. All new compounds were synthesized and their stereoisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Finally, the planar structure of 2 was constructed as shown in Figure 1. Comparing the structure of 2 with that of one known compound, 6-[2 0 -propyloxiran-1-yl]-2H-pyran-2-one isolated from Trichoderma viride UCA 06 [14], we found that both compounds have the same 2-propyloxiran-1-yl moiety attached to C-6 position. Significantly, the absolute configuration of 2-propyloxiran-1-yl moiety in 6-[2 0 -propyloxiran-1-yl]-2H-pyran-2-one has been determined to be 1S, 2R through chemical synthesis of its stereoisomers.…”
Section: Resultsmentioning
confidence: 93%
“…Finally, the planar structure of 2 was constructed as shown in Figure 1. Comparing the structure of 2 with that of one known compound, 6-[2 0 -propyloxiran-1-yl]-2H-pyran-2-one isolated from Trichoderma viride UCA 06 [14], we found that both compounds have the same 2-propyloxiran-1-yl moiety attached to C-6 position. Significantly, the absolute configuration of 2-propyloxiran-1-yl moiety in 6-[2 0 -propyloxiran-1-yl]-2H-pyran-2-one has been determined to be 1S, 2R through chemical synthesis of its stereoisomers.…”
Section: Resultsmentioning
confidence: 93%
“…The transcription factor Thctf1 also regulates the biosynthesis of 6PP in T. harzianum. Chromatographic and spectroscopic analyses showed that Thctf1 null mutants did not produce two secondary metabolites derived from 6PP (6-[(1 R,2 S)dihydroxypentyl]-2H-pyran-2-one and 6-((1 S,2 R)-2propyloxiran-1-yl)-2H-pyran-2-one) and not previously described in the Trichoderma genus, that are present in wildtype culture filtrates [26,27].…”
Section: Pyronesmentioning
confidence: 84%
“…Among all the compounds recorded in GC-MS Chromatography of hexane extracts of fungal endophytes 2H-pyran-2-one, 5,6-dihydro-6-pentyl, palmitic acid, methyl ester, oleic acid are reported to have antifungal activity [ 44 ], [ 45 ]. Therefore, in order to confirm the contributory effect of these compounds on the antifungal activity of hexane extracts of endophytic fungi, they were procured from commercial sources and their antifungal activity was evaluated against phytopathogens.…”
Section: Resultsmentioning
confidence: 99%